PENGARUH GREEN MARKETING TERHADAP MINAT BELI PRODUK AVOSKIN (STUDI KASUS PADA FOLLOWERS AKUN TWITTER @AVOSKINBEAUTY) - Irma Sari Gani; Dian Pane; Farida Amansyah (Journal of Business Administration (JBA), 2022)
This research was conducted on followers of @avoskinbeauty twitter account. This research aimed to find out the effect of green marketing on buying interest in Avoskin products on the followers of @avoskinbeauty twitter account. The type of research used was associative research. Sampling technique used was stratified purposive sampling. Data collection techniques were carried out using questionnaires distributed to 100 followers of @avoskinbeauty twitter account. The data obtained were analyzed using simple linear regression analysis, coefficient of determination and t-test with the help of SPSS 25.0 program. The results of this research indicated that green marketing had a positive and significant effect on buying interest in Avoskin products on followers of @avoskinbeauty twitter account. Green marketing contributes 28.3% in influencing the buying interest of followers of the @avoskinbeauty twitter account towards Avoskin products.